How Does the Diagnostic Effectiveness of Transbronchial Needle Aspiration/Transbronchial Biopsy With Radial Endobronchial Ultrasound for the Diagnosis of Peripheral Pulmonary Lesions Differ With and Without a Guide Sheath? - Ito, Takayasu; Chrétien, Basile; Nishida, Kazuki; Kimura, Hayata; Baba, Tomoya; Makino, Yasushi; Ikenouchi, Tadasuke; Tanaka, Ichidai; Sakamoto, Koji; Shindo, Yuichiro; Ishii, Makoto (Journal of Bronchology & Interventional Pulmonology, 2025)
BACKGROUND: The diagnostic yield of virtual bronchoscopy with radial endobronchial ultrasound (r-EBUS) for peripheral pulmonary lesions (PPLs) remains unsatisfactory because of limited lesion access by biopsy instruments. r-EBUS-guided transbronchial needle aspiration (TBNA) followed by transbronchial biopsy (TBB) (TBNA/TBB) with a guide sheath (GS) potentially increases the PPL diagnostic yield as the needle penetrates the bronchial wall, enabling subsequent forceps biopsy closer to the lesion. However, regarding the application of r-EBUS-guided TBNA/TBB for PPL diagnosis, data on the diagnostic yield of TBNA/TBB with a GS are limited compared with those on TBNA/TBB without a GS. METHODS: We conducted a retrospective analysis of consecutive patients who underwent r-EBUS-guided TBNA/TBB for PPLs with or without a GS at 3 institutions. The objective was to evaluate the effect of GS usage on diagnostic yield of PPLs, focusing on lesion location from the hilum on computed tomography. To estimate the probability of successful diagnosis based on GS status, we applied an adjusted logistic regression model with inverse probability of treatment weighting to account for potential confounding. RESULTS: The interaction between GS usage and lesion location was significant (odds ratio=14.19; 95% CI: 1.48-135.75). The rates of successful diagnosis were 83% and 75% for lesions within the middle third ellipse during no and GS use, respectively, and 44% and 87% for lesions within the outer third ellipse during no and GS use, respectively. CONCLUSION: This study demonstrated that GS use in r-EBUS-guided TBNA/TBB improves diagnostic success for lesions within the outer third ellipse.